1994
DOI: 10.1523/jneurosci.14-03-01856.1994
|View full text |Cite
|
Sign up to set email alerts
|

Topographic organization of the reciprocal connections between the monkey entorhinal cortex and the perirhinal and parahippocampal cortices

Abstract: The perirhinal and parahippocampal cortices constitute the major sources of cortical input to the monkey entorhinal cortex. Neuropsychological studies have shown that these three cortical regions contribute in an important way to normal memory function. We have investigated the topographic and laminar organization of the reciprocal projections between the entorhinal cortex and these two adjacent cortical areas by placing anterograde and retrograde tracers in all three regions. There were three major findings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
464
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(505 citation statements)
references
References 53 publications
40
464
1
Order By: Relevance
“…Intracellular recordings show that the initial sink is due to monosynaptic EPSPs, and the later is due to polysynaptic EPSPs (Biella et al, 2001). Conversely, PR (BA36) projects widely to layer I in IT (Lavenex et al, 2002), and also within itself (Suzuki and Amaral, 1994). These studies suggest that the initial middle layer sink noted in the current study represents excitatory input from lower cortical areas; the following middle layer sink represents a period when the predominant excitatory input is feedforward; and the final superficial layer sink a period when top-down and local association afferents predominate.…”
Section: Intracolumnar and Intercolumnar Circuitry Of Word Processingmentioning
confidence: 99%
“…Intracellular recordings show that the initial sink is due to monosynaptic EPSPs, and the later is due to polysynaptic EPSPs (Biella et al, 2001). Conversely, PR (BA36) projects widely to layer I in IT (Lavenex et al, 2002), and also within itself (Suzuki and Amaral, 1994). These studies suggest that the initial middle layer sink noted in the current study represents excitatory input from lower cortical areas; the following middle layer sink represents a period when the predominant excitatory input is feedforward; and the final superficial layer sink a period when top-down and local association afferents predominate.…”
Section: Intracolumnar and Intercolumnar Circuitry Of Word Processingmentioning
confidence: 99%
“…Second, because humans with damage to the perirhinal cortex demonstrate normal visual perception as evidenced by intact visual recognition performance with very short delays (Buffalo et al 1998a), whereas area TE has been proposed to play a role in visual perceptual processing (Iwai and Mishkin 1968;Gross 1973;Dean 1976;Buffalo et al 1998b), we reasoned that the two areas might differ in their contributions to visual short-term memory and visual long-term memory. Third, the perirhinal cortex receives direct input from visual areas upstream from area TE (Suzuki and Amaral 1994a), and area TE does not project exclusively to the perirhinal cortex but also originates direct prefrontal and parietal cortical projections as well as subcortical projections to the caudate nucleus (Van Hoesen et al 1981;Saint-Cyr et al 1990;Webster et al 1994). Accordingly, we reasoned that it might be possible to demonstrate a dissociation between the effects of lesions of the perirhinal cortex and area TE on two tasks that involved different kinds of visual discrimination.…”
Section: Introductionmentioning
confidence: 98%
“…Area TE lies immediately adjacent and lateral to the perirhinal cortex and is considered to be the last exclusively visual area in the ventral visual processing stream (Ungerleider and Mishkin 1982). Area TE also originates strong anatomical projections to perirhinal cortex and receives projections from it (Suzuki and Amaral 1994a). With respect to the perirhinal cortex, studies in humans, monkeys, and rats have demonstrated that lesions of perirhinal cortex (or deactivation by cooling) impair performance on tests of learning and memory (Horel et al 1987;Bachevalier et al 1993;Mumby and Pinel 1994;Ennaceur et al 1996;Ennaceur and Aggleton 1997;Buffalo et al 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that IT cortex receives direct and indirect backward projections from the perirhinal and entorhinal cortex (10)(11)(12)(13). The hypothesis for the role of the backward connections predicts that the lesion of the perirhinal and entorhinal cortex would impair the formation of the associative code for pictures in the IT cells.…”
mentioning
confidence: 99%